Impact of the pandemic on the bakery market: from the perspective of a factory in Teresina (Research, Society and Development, 2022)
The bakery industry is a segment that operates in almost all cities in the country, and just like most economic sectors, it also suffered from the effects of the coronavirus pandemic, facing challenges such as the SELIC that makes access to credit more expensive, DOLÁR which impacts on commodity prices, COVID which is causing a collapse in the world economy and IPCA which reflects on product inflation. Thus, this study aims to demonstrate how the pandemic impacted product sales in the bakery sector. A quantitative research was then carried out to analyze the sales behavior of a company that operates in the segment. In view of this, a cross-section was carried out for analysis and interpretation of data through two regressions using the Shapire -Wilker test, where it was possible to conclude that the bakery market has been showing a constant process of recovery in the market.